What is the easier and more reliable dose calculation for iv Phenytoin in children at risk of developing convulsive status epilepticus, 18 mg/kg or 20 mg/kg? - Prasad, Manish; Shenton, Priya; Dietz, Sanne; Saroha, Vivek; Whitehouse, William P. (BioMed Central, 2013)
Background: With the Convulsive Status Guidelines due for renewal, we wondered if a phenytoin dose of ‘20 mg/kg’ would be easier to calculate correctly and therefore safer than the current ‘18 mg/kg’. An educational exercise in dose calculation was therefore undertaken to assess ease of calculation. Method: A standard question paper was prepared, comprising five clinical scenarios with children of varying ages and estimated body weights. Medical students, trainee doctors at registrar and senior house officer level, and consultant paediatricians were asked to complete the exercise, in private, by one of two medical students (SD, PS). Calculations were done with and without a calculator, for 18 mg/kg and for 20 mg/kg in randomised order. Speed and errors (greater than 10%) were determined. The data analysis was performed using SPSS version 18. Results: All answered all 20 scenarios, giving a total of 300 answers per doctor/student group, and 300 answers per type of calculation. When comparing the 2 doses, the numbers of errors more than 10% were significantly less in 20 mg/kg dose (0.33%) as compared to the 18 mg/kg dose (9.3%) (p<0.0001). Speed off calculation was significantly decreased in 20 mg/kg dose when compared with 18 mg/kg dose, with (p<0.001) or without (p<0.0001) the calculator. Speed was more than halved and errors were much less frequent by using a calculator, for the 18 mg/kg dose but no difference with or without the calculator for 20 mg/kg dose. Conclusion: We recommend that the future guidelines should suggest iv Phenytoin at 20 mg/kg rather than 18 mg/kg. This will make the calculation easier and reduce the risk of significant errors.